2011 IEEE International Geoscience and Remote Sensing Symposium 2011
DOI: 10.1109/igarss.2011.6050002
|View full text |Cite
|
Sign up to set email alerts
|

Airborne polarimetric, two-color laser altimeter measurements of lake ice cover: A pathfinder for NASA's ICESat-2 spaceflight mission

Abstract: The ICESat-2 mission will continue NASA's spaceflight laser altimeter measurements of ice sheets, sea ice and vegetation using a new measurement approach: micropulse, single photon ranging at 532 nm. Differential penetration of green laser energy into snow, ice and water could introduce errors in sea ice freeboard determination used for estimation of ice thickness. Laser pulse scattering from these surface types, and resulting range biasing due to pulse broadening, is assessed using SIMPL airborne data acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…These are much more sensitive to low intensity signals, requiring lower powered lasers and so making the instrument lighter and cheaper. NASA's SIMPL (Dabney et al, 2010) and ICESat II (Harding et al, 2011) instruments currently in development are examples and Moussavi, Abdalati, Scambos, and Neuenschwander (2014) demonstrated that they can measure forest height. However they require repeated measurements to measure energy, either from a fixed position (Hernandez-Marin, Wallace, & Gibson, 2007;Wallace et al, 2012) or by averaging over an area (Moussavi et al, 2014), which introduces statistical errors on top of the error from inversion methods.…”
Section: System Pulsementioning
confidence: 98%
“…These are much more sensitive to low intensity signals, requiring lower powered lasers and so making the instrument lighter and cheaper. NASA's SIMPL (Dabney et al, 2010) and ICESat II (Harding et al, 2011) instruments currently in development are examples and Moussavi, Abdalati, Scambos, and Neuenschwander (2014) demonstrated that they can measure forest height. However they require repeated measurements to measure energy, either from a fixed position (Hernandez-Marin, Wallace, & Gibson, 2007;Wallace et al, 2012) or by averaging over an area (Moussavi et al, 2014), which introduces statistical errors on top of the error from inversion methods.…”
Section: System Pulsementioning
confidence: 98%
“…In addition, retrievals from single channel observations require high accuracy in absolute calibration. To achieve better retrievals, multi wavelength lidar observations, such as the ones made the Slope Imaging Multi-polarization Photon-counting Lidar (SIMPL) [23,24], are needed. SIMPL acquired data over a range of grain size conditions in Greenland during July and August 2015.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The non-imaging airborne spectrometers and SIMPL (Dabney et al, 2010;Harding et al, 2011) were flown together on a National Aeronautics and Space Administration (NASA) Langley Research Center King Air (hereinafter UC-12B). SIMPL uses a micropulse, photon-counting, multibeam measurement like that of ATLAS but provides added information about light scattering by using co-aligned green and NIR laser pulses and a measure of pulse depolarization.…”
Section: Introductionmentioning
confidence: 99%